Home gardening and associations with fruit and vegetable intake and BMI. Issue 18 (3rd December 2020) - Kegler, Michelle C; Prakash, Radhika; Hermstad, April; Williamson, Dana; Anderson, Kate; Haardörfer, Regine
Abstract: Objective: To understand who engages in home gardening and whether gardening is associated with fruit and vegetable intake and weight status. Design: A national cross-sectional survey. Setting: Online survey panel in the USA. Participants: Adults aged 18–75 years representing the US population with respect to gender, age, race/ethnicity, income and geographic region ( n 3889). Results: Approximately 30 % of survey respondents reported growing edible plants in a home garden. Gardeners were more likely to be White or Asian, employed, have higher income, be married, have children in the household and live in rural areas. Gardeners were less likely to be obese and more likely to meet US dietary recommendations for fruit and vegetable consumption. In multivariable analyses, home gardens remained associated with fruit and vegetable intake and BMI when controlling for a range of socio-demographic characteristics and level of rurality. Conclusions: The current study identifies who is gardening in the USA and provides useful information for public health efforts to increase gardening as a nutrition intervention. Future research should examine the benefits of home gardening and interventions to increase home gardening using more rigorous designs.